Sulfated polysaccharides derived from marine microalgae, Synechococcus sp. VDW, inhibit the human colon cancer cell line Caco-2 by promoting cell apoptosis via the JNK and p38 MAPK signaling pathway - Srimongkol, Piroonporn; Songserm, Pajareeya; Kuptawach, Kittisak; Puthong, Songchan; Sangtanoo, Papassara; Thitiprasert, Sitanan; Thongchul, Nuttha; Phunpruch, Saranya; Karnchanatat, Aphichart (My University, 2023)
This study offers an examination of the physicochemical qualities of marine microalgae-derived sulfated polysaccharides (MMPS) from Synechococcus sp. VDW along with an investigation of their antioxidant and antitumor activities. On average, MMPS offered a molecular weight of 190.94 kDa with sulfate content of 16.83 %. There were shown to be four different monosaccharides contained within MMPS. The anticancer characteristics of human colon cancer cell lines (Caco-2) were also investigated. Flow cytometry revealed that MMPS triggered apoptosis at doses of 1 mg mL−1. Meanwhile, analysis of gene and apoptosis protein expression demonstrated that MMPS increased apoptosis in Caco-2 cells via the p38 MAPK and JNK signaling pathways. These findings contribute to our current understanding of how MMPS helps promote tumor suppression. In conclusion, the possibility that MMPS may possess anticancer qualities in the treatment of human colon cancer makes it an appealing candidate for anticancer polysaccharide combinations with chemotherapeutic agents and functional foods.
Keywords: Anticancer; Antioxidant; Apoptosis; Colon cancer; Marine microalgae; Sulfated polysaccharides